Randomized, controlled, double-blinded field trial to assess Leishmania vaccine effectiveness as immunotherapy for canine leishmaniosis. Issue 43 (15th October 2018) - Toepp, Angela; Larson, Mandy; Wilson, Geneva; Grinnage-Pulley, Tara; Bennett, Carolyne; Leal-Lima, Adam; Anderson, Bryan; Parrish, Molly; Anderson, Michael; Fowler, Hailie; Hinman, Jessica; Kontowicz, Eric; et al.
Highlights: Blinded clinical field trial. Anti- Leishmania vaccine as immunotherapy significantly reduced clinical progression. Vaccine decreased mortality in Leishmania infantum -infected, healthy, dogs. Abstract: Better tools are necessary to eliminate visceral leishmaniasis (VL). Modeling studies for regional Leishmania elimination indicate that an effective vaccine is a critical tool. Dogs are the reservoir host of L. infantum in Brazil and the Mediterranean basin, and therefore are an important target for public health interventions as well as a relevant disease model for human VL. No vaccine has been efficacious as an immunotherapy to prevent progression of already diagnostically positive individuals to symptomatic leishmaniasis. We performed a double-blinded, block-randomized, placebo-controlled, vaccine immunotherapy trial testing the efficacy of a recombinant Leishmania A2 protein, saponin-adjuvanted, vaccine, LeishTec®, in owned hunting dogs infected with L. infantum . The primary outcome was reduction of clinical progression, with reduction of mortality as a secondary outcome. Vaccination as an immunotherapy reduced the risk of progression to clinically overt leishmaniasis by 25% in asymptomatic dogs (RR: 1.33 95% C.I. 1.009–1.786 p-value: 0.0450). Receiving vaccine vs. placebo reduced all-cause mortality in younger asymptomatic dogs by 70% (RR: 3.19 95% C.I.: 1.185–8.502 p-value = 0.0245). Vaccination of infected-healthy animals with an anti- Leishmania vaccine significantly reduced clinical progression and decreased all-cause mortality. Use of vaccination in infected-healthy dogs can be a tool for Leishmania control.